If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 6x = 3x + -15 Reorder the terms: 9 + 6x = -15 + 3x Solving 9 + 6x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + 6x + -3x = -15 + 3x + -3x Combine like terms: 6x + -3x = 3x 9 + 3x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + 3x = -15 + 0 9 + 3x = -15 Add '-9' to each side of the equation. 9 + -9 + 3x = -15 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = -15 + -9 3x = -15 + -9 Combine like terms: -15 + -9 = -24 3x = -24 Divide each side by '3'. x = -8 Simplifying x = -8
| onehalfx+3=7 | | -5x+8=-7x-16 | | 4.5=34.5-3w | | 4ln(6y-1)=36 | | x-5-10=15 | | 0.72x+0.5=0.3-0.27x+0.3 | | -5x+1=2-6x | | x+4=7.5 | | -5x+1=5x-9 | | -X+8.5=14.2 | | 3x-9=-73-5x | | forx=7 | | 8+4x=-4x+80 | | 8x+16=23 | | 4(x+1)+3x+7=52 | | -8+2x=-7x+73 | | 3(w+6)= | | (1/3)3.14*4*3^2 | | 3.4q-3.2-2.6q=-0.2q-4.8 | | X+10=7x-26 | | Since=0.48 | | 2x^2-16+20=0 | | 10=z/6-2 | | 3(x-1)+3-2x=4 | | 9x^2+7=8 | | (1/3)^3.14*4*3^2 | | 15/x=x-2 | | 8f+9=15 | | 5c+1=-1+6x | | 3(y-6)-5y= | | 8+5x=-4x+80 | | (4x+1)(x-6)=0 |